P18 Clinical management of intestinal-type sinonasal adenocarcinoma: A monoinstitutional experience of 165 cases. Issue 5 (May 2015) - Costales, M.; López, F.; Vivanco, B.; García-Inclán, C.; López-Hernández, A.; Hermsen, M.; Llorente, J.L.
Abstract : Introduction: Intestinal-type sinonasal adenocarcinomas (ITAC) are rare tumors, related to occupational exposure to wood and leather dust. Patients with ITAC carry a poor prognosis and recurrent disease is the main cause of mortality. The low incidence of ITAC has hampered diagnosis, genetic analyses, classification, and staging, and prevented the accumulation of clinical experience at individual institutions. The aim of this study was to describe the clinical, pathological and follow-up data of a large series of cases treated in one single institute. Material and methods: A total of 165 patients diagnosed with ITAC and treated in our hospital between 1978 and 2014 were included and the following variables were studied: gender, age, etiological factors, histopathological features, localization, surgical approaches, complementary treatment, clinical evolution and survival. Results: The great majority of patients was male (164/165), the median age was 65 years (28–92 years), and 87% had a history of wood dust exposure. All tumors were localized in the ethmoid sinus, the most frequent histological subtype being colonic, followed by mucinous, papilar and solid type. At the time of presentation, 13% showed intracranial, 19% dura mater and 13% periorbital involvement, in total 34% of cases were stage III and 32% stage IV. The main treatment was the surgery, with different surgical approaches including craneofacial resection, craneofacial endoscopic resection and maxillectomy. Complementary radiotherapy was given in 95% of the patients. On average, patients remained 18 months disease-free and the overall 5-year survival was 45%. Conclusion: Advances in surgical and radiotherapeutic approaches have improved management of ITAC although limited progress has been made in chemotherapy, partly owing to the difficulty of recruiting a sufficient number of patients for clinical trials. The study of molecular tumorigenic pathways and the testing of alternative treatment strategies would greatly benefit from wider multi-institutional collaboration, and we strongly support such collaborative efforts.